Employee Satisfaction and Performance Influence on Green Work Behavior in Green HRM: Literature Review - Laksana, Michael Ardian; Nurmasari, Salwa Salsabila; Kurniawan, Herdi; Raharja, Edy (LifeSciFi, 2024)
The growing emphasis on environmental sustainability has propelled the adoption of Green Human Resource Management (Green HRM) practices. Green Human Resource Management (Green HRM) refers to the integration of environmental management into human resource practices. It encompasses the development and implementation of sustainable HR policies that promote environmental stewardship within the workplace. This literature review examines the relationships between employee satisfaction, performance, and green work behavior within the context of Green HRM using quantitative methods. Green HRM integrates sustainable practices into HR policies to promote environmental stewardship in the workplace. The review analyzes quantitative data from surveys and performance metrics to assess how employee satisfaction influences performance and how both factors impact green work behavior. Findings indicate a positive correlation between employee satisfaction and performance, with significant implications for green work behavior. Future research should develop tailored strategies to enhance these aspects, thereby maximizing the potential of Green HRM in promoting sustainability and organizational effectiveness.